SHAPING INDONESIA’S 2045 GENERATION: TEACHER EMPOWERMENT STRATEGIES FOR RELIGIOUS CHARACTER BUILDING IN EARLY CHILDHOOD - Celia Cinantya; Ahmad Suriansyah; Aslamiah Aslamiah; Novitawati Novitawati (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to explore how teacher empowerment strategies are implemented in early childhood education settings, identify professional, institutional, and contextual factors influencing teachers’ capacity to foster religious character, and examine how these strategies contribute to the development of religious character as a foundation for long-term national development.Methodology – Using qualitative research methods, this study explores the experiences and perceptions of principals and teachers regarding strengthening religious-based character for early childhood. The subjects of this study were Principals, Teachers, and parents at PAUD Al Firdaus, Banjarmasin. Data were collected through in-depth interviews, observations, and documentation studies. Data validity tests used Triangulation Techniques. Data analysis used Miles & Huberman's analysis techniques, consisting of data condensation, data presentation, drawing, and verifying conclusions.Findings – Teacher empowerment is implemented through continuous professional development, leadership trust and autonomy, institutional support, and systematic monitoring and evaluation. Teachers' capacity to foster religious character is influenced by professional competence, supportive school culture, leadership commitment, parental involvement, and the availability of learning resources. Furthermore, empowered teachers demonstrate greater creativity, consistency, and commitment in integrating religious values into daily learning routines and habituation practices, leading to observable improvements in children's moral attitudes, religious behaviors, and social interactions.Contribution – This study concludes that teacher empowerment is a critical foundation for sustainable religious character development in early childhood and serves as a strategic investment in building ethically grounded human capital aligned with Indonesia’s Vision 2045